(untitled) (LACCEI, 2024)
Abstract– The objective of this research is to analyze the relationship between the company’s organizational innovation, the company’s innovation capacity process, product innovation and the creativity of employees in a Tech based company in the Dominican Republic. A quantitative methodology was used, based on the application of a validated survey. The data were analyzed with the SPSS and PLS programs. The results show a positive influence of organizational innovation on the company’s innovation capacity process, as well as on product innovation and creativity. Keywords– innovation, process, service, creativity, business